Pengaruh Kebijakan Tarif Listrik Adjustment terhadap Konsumsi Listrik Rumah Tangga di Indonesia - Agustin, Rima; Wikarya, Uka (Jurnal Kebijakan Ekonomi, 2020)
In determining electricity tariffs in Indonesia, it has changed since 2015, namely by the policy of tariff adjustments or adjustments to electricity tariffs by adjusting to macro indicators namely ICP, exchange rates and inflation. This paper will examine the impact of the tariff adjustment policy on Indonesia's household electricity consumption. By using the Ordinary Least Square (OLS) regression method, the results show that the effect of electricity prices on electricity consumption is negative and insignificant, which means that the effect of changes in electricity prices on household electricity consumption is very small. From this study also added control variables from the social, economic and building aspects that can affect household electricity consumption pattern.